Production of fodder in a treeless system and in silvopastoral system in central Argentina - Plevich, José Omar; Gyenge, Javier; Sánchez Delgado, Ángel; Tarico, Juan Carlos; Fiandino, Santiago; Utello, Marcos Jesús (Instituto de Florestas da Universidade Federal Rural do Rio de Janeiro, 2019)
This paper aims to identify the spatial and temporal distribution of net aerial primary production (NAPP) of oats and sorghum in silvopastoral systems (SPS) and in a treeless situation (TLS), in Southern Cordoba, Argentina. The silvopastoral systems are composed of three woody cultures (Pinus elliottii, Eucalyptus viminalis and Quercus robur), and two grass species (Avena sativa and Sorghum sudanense). NAPP of Avena sativa and Sorghum sudanense were lower in the silvopastoral systems than in the treeless situation. However, there were also differences in terms of NAPP according to the tree species, and these differences were related to the intensity of competition between trees and grasses. Pinus elliottii and Quercus robur were less competitive than Eucalyptus viminalis, which might be associated with their morphophysiological differences, their differential growth rate and their differences in terms of phenology. Finally, facilitation effects between trees and grasses were also identified under certain conditions.